Comparative Analysis of Real-Time Fluorescence-Based Spectroscopic Instruments: Bioaerosol Detection in the Urban Environment of Dublin City, Ireland - Jerry Hourihane Clancy; Emma Markey; Moisés Martínez-Bracero; José María Maya-Manzano; Eoin J. McGillicuddy; Gavin Sewell; Roland Sarda-Estève; Dominique Baisnée; Andrés M. Vélez-Pereira; Gemma Davis; David J. O’Connor (Atmosphere)
Primary Biological Aerosol Particles (PBAPs) range in size from a few nanometres to hundreds of micrometres and include particles such as pollen and fungal spores, which are significant due to their prevalence and potential to induce allergic reactions and other health-related issues. This study employs real-time fluorescence spectroscopy devices, the Wideband Integrated Bioaerosol Sensor (WIBS-NEO) and IBAC-2, to monitor PBAPs in the urban environment of Dublin, Ireland, during a six-week campaign in the summer of 2019. The WIBS-NEO demonstrated moderate correlations (R2 = 0.5–0.7) in comparison with Hirst volumetric air sampler data for pollen and fungal spore concentrations following appropriate data filtering. In contrast, the IBAC-2 showed poor correlation with ambient fungal spore concentrations and lacked the necessary particle size ranges for reliable pollen measurement. Comparative analysis between WIBS-NEO and IBAC-2 revealed moderate correlation (R2 ≈ 0.6) for small fluorescent particles (fluorescent particles between 0.7 and 1.5 μm optical diameter) but lower correlation for larger particles and specific bioaerosol types. The findings suggest that while the WIBS-NEO is effective for real-time bioaerosol monitoring, further refinement is needed for IBAC-2. This study underscores the potential of using advanced real-time monitoring tools in urban environments and highlights the need for continued development to address current limitations.